Studies on tissue distribution of scutellarin and methyl polyethylene glycol (mPEG)-scutellarin prodrug in mice - Juan Lu; Xia Zhan; Qingfei Liu; Xi Chen; Xinge Zhao; Yiming Wang; Guoan Luo (Elsevier, 2012)
This study was to determine tissue distribution and pharmacokinetics of mPEG-scutellarin prodrug (7e), a chemical entity previously shown to have a beneficial effect in cerebral ischemia/reperfusion (I/R) injury. After injecting scutellarin or prodrug 7e, the concentrations of scutellarin and 7e in tissues were determined and the pharmacokinetic parameters were calculated. The results showed that the distribution of scutellarin in tissues was enhanced by PEGylation. The distribution of 7e in brain was approximately 2.1-fold higher than that of scutellarin, indicating that PEGylation increased the brain penetration of scutellarin. We conclude that 7e could exert more effective protection on cerebral I/R injury in mice. This study also provided a simple and convenient strategy to identify novel drugs with potential protective function for I/R injury in mice.